HISTORICAL DEVELOPMENT IN INDIAN FOREIGN POLICY (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Indian foreign policy is come on era of Nehru, he is the main founder of Indian foreign policy. The main bases of Nehru policy are as independent & autonomy in foreign policy, policy of economic development, panchseel policy, policy of unity with Asian & African country, non-aligned movement. Indian foreign policy is also get change with period of Indra Gandhi in 1971 Bangladesh war fought with Pakistan and in 1974 India can peaceful nuclear explosion. On term of Rajiv Gandhi govt.it make an effective relationship with neighbourhood and it also facing the challenge of ethnic crisis in Sri Lanka. In the tenure of Narasimha Rao India foreign policy see towards the east because this area is economically developed and policy decision to move economy as liberalization, privatization and globalization (LPG). In Vajpayee govt. Primarily its main foreign policy came into area to development of nuclear weapons, India get membership of G-8 and trying to improve relations with Pakistan by starting Bus trip India to Lahore. In Manmohan Singh’s govt. the foreign policy was successful in India-US civil nuclear cooperation agreement and in 2005 Indian foreign policy see towards the west. In present Modi government it accepted Indian foreign policy as first neighbourhood policy, economic development, cultural diplomacy, act east policy, Indian diaspora and the security. We have observed that clearly the development of Indian foreign policy in present is not yet change in qualitative but it can improve in quantitative.